2014
DOI: 10.1097/prs.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fat Transfer Viability

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…[ 18 ] Novel strategies have thus been employed to enhance cytoprotection of the ASCs at the target site, which includes ischaemic preconditioning, pharmacological therapy, refinement of liposuction techniques to minimise trauma, as well as the addition of growth factors. [ 5 19 20 ] Future experimental work will be centred on safe and Food and Drug Administration - approved agents, which may be administered in conjunction with ASC transplantation to maximise the therapeutic efficacy at the target site.…”
Section: Clinical and Experimental Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Novel strategies have thus been employed to enhance cytoprotection of the ASCs at the target site, which includes ischaemic preconditioning, pharmacological therapy, refinement of liposuction techniques to minimise trauma, as well as the addition of growth factors. [ 5 19 20 ] Future experimental work will be centred on safe and Food and Drug Administration - approved agents, which may be administered in conjunction with ASC transplantation to maximise the therapeutic efficacy at the target site.…”
Section: Clinical and Experimental Trialsmentioning
confidence: 99%
“…have demonstrated that adipocyte viability was greater in the lower abdomen as compared to the flanks. [ 19 ]…”
Section: Isolation and Harvesting Of Adipose Stem Cellsmentioning
confidence: 99%
“…In addition to that our research's lack of data regarding patients' age, BMI, and estrogen status as increasing evidence seems to correlate these variables to clinical outcome [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose the abdominal area as the donor site, as recommended in the recent literature. 5 We used the FAT WASHER system (Groupe SEBBIN, Boissy L’Aillerie, France), a closed system for washing and decanting fat, thus avoiding centrifugation. After infiltration of the donor area with Klein solution, a 3-mm accelerator-type cannula was used to harvest the fat with limited vacuum (0.4 atm).…”
Section: Case Reportmentioning
confidence: 99%